Transformasi Respon Vokal Gadih Basanai dalam Komposisi Musik Basauikan Berbasis Tradisi Ronggeang Pasaman - Yunaidi Yunaidi; Arnailis Arnailis; Asep Saepul Haris (LPPM Institut Seni Indonesia Padangpanjang, 2026)
This article discusses the transformation of vocal response in the song Gadih Basanai from the Ronggeang performing art of Pasaman into a new musical composition entitled Basauikan. Ronggeang is a traditional performing art of Pasaman, West Sumatra, which combines music, dance, singing, pantun, and interaction between performers and audiences. One of the distinctive musical features of Gadih Basanai is the vocal response at the end of the lyrical phrase, collectively performed by musicians and audiences. This musical phenomenon became the main creative basis for the composition of Basauikan. This artistic creation applied a tradition-based practice method through observation, interviews, discussion, musical exploration, studio work, and performance realization. The result shows that vocal response can be transformed not only as a vocal element but also as a compositional principle through call and response, unisono, tempo changes, melodic fragmentation, repetition, modulation, accentuation, and timbral development involving violin, gandang, Minangkabau zither, metal talempong, accordion, bass guitar, and vocals. Basauikan demonstrates that tradition can serve as a source of new musical creation while maintaining its local musical identity. This article emphasizes the importance of tradition-based musical creation as a strategy for preserving, developing, and renewing regional performing arts.